Play time: gender, anti-semitism and temporality in medieval biblical drama - Black, Daisy (Manchester medieval literature and culture, 2020)
This book presents an important re-theorisation of gender and anti-Semitism in medieval biblical drama. It charts conflicts staged between dramatic personae in plays that represent theological transitions, including the Incarnation, Flood, Nativity and Bethlehem slaughter. Interrogating the Christian preoccupation with what it asserted was a superseded Jewish past, it asks how models of supersession and typology are subverted when placed in dramatic dialogue with characters who experience time differently. The book employs theories of gender, performance, anti-Semitism, queer theory and periodisation to complicate readings of early theatre’s biblical matriarchs and patriarchs. Dealing with frequently taught plays as well as less familiar material, the book is essential reading for specialist, undergraduate and postgraduate researchers working on medieval performance, gender and queer studies, Jewish-Christian studies and time